Prevalencia de Brucelosis Bovina (Brucella abortus) mediante los métodos de detección como la prueba del Milk Ring Test (MRT) y la prueba de Elisa Competitiva (Elisa-C). Una Revisión descriptiva (2021)
Studies on Bovine Brucelossis (Brucella abortus) through detection methods such as the Milk Ring Test (MRT) and the Competitive Elisa test (Elisa-C), argue that Bovine Brucelossis is an infectious disease known as infectious abortion that It affects bovines in all age ranges more frequently in sexually adult animals in dairy and dairy herds, hence the need for detection methods such as the Milk Ring Test (MRT) or also called the milk ring test. (PAL) used for the diagnosis of brucellosis in herds.1. Identify the peculiarities of bovine brucellosis to determine the prevalence and characteristics of the disease. 2. Analyze detection methods such as the Milk Ring Test (MRT) and the Competitive Elisa test (Elisa-C), to find out in different international and national studies that progress has been made with the analysis of bovine Brucellosis. 3. Establish an adequate management plan for diagnosis and control in the prevention of bovine brucellosis disease. Implement the Milk Ring Test (MRT) and Elisa-C diagnostic methods, as they have the advantage over serological tests (taken in an invasive way), which stress the animal with the consequent loss of milk production or other undesirable effects such as product of the handling of the moment of taking the sample.The study’s conclusion referenced in this investigation determined results of high concordance between the detection methods Milk Ring Test (MRT) or also called Milk Ring Test (PAL) and the Elisa-C method, in relation to detecting IgG antibodies. and IgM (which are immunoglobulins or antibodies in blood serum), bound to fat globules in milk and to a pure abortus culture preparation, which form a ring at the top of the milk column and on positive readings This makes it possible to observe agglutination at the bottom of the tube and occasionally agglutination flakes dispersed in the milk column, thus obtaining better results in disease surveillance.